Implant Prosthodontic Rehabilitation after Surgical Treatment for an Oropharyngeal Malignant Tumour Using Tantalum Dental Implants - Marko Vuletić; Ivica Pelivan; Dragana Gabrić (Hindawi Limited, 2021)
Oropharyngeal cancer (OPC) represents a significant portion of head and neck cancers. In most cases, it is localised in the soft palate, lingual and palatine tonsils, base of the tongue, and the surrounding tissues. Alcohol and tobacco exposure are well-known evidence-based risk factors for developing OPC; however, over the last decade, there has been a rapid increase in OPC linked to human papillomavirus (HPV). Dental implant therapy faces many challenges related to immediate and long-term success, and patients who are rehabilitated with implant prosthodontic therapy often have numerous comorbidities. Tantalum is a rare transitional metal element which has high corrosion resistance and is extremely inert. Porous tantalum trabecular metal (PTTM) has high volumetric porosity, a low modulus of elasticity, and very high friction. PTTM implant surface enhancement allows "osseoincorporation," which means the neovascularisation and formation of new bone directly onto the implant. A 65-year-old patient presented to the Department of Oral Surgery of Clinical Hospital Centre Zagreb after resection of the mandible due to OPC had oral rehabilitation. Three Zimmer Biomet Trabecular Metal™ implants (4.1×10 mm) were inserted in the area of lower left first incisor, lower left second premolar, and lower right second premolar, and after four months, a new upper partial denture and the bar-retained mandibular overdenture were made. Implant prosthodontic rehabilitation of head and neck cancer patients is usually challenging in terms of achieving an improvement in its main aim, quality of life; however, today it is a safe and reliable therapy. Although radiation therapy may negatively affect the patient's oral condition and influence the short- and long-term success of the implant, the presented case report showed that the excellent properties of PTTM-enhanced dental implants may give great basis for future comparative researches of using these implants in the treatment of oncologic patients.